1970
DOI: 10.1029/ja075i031p06342
|View full text |Cite
|
Sign up to set email alerts
|

World contours of conjugate mirror locations

Abstract: The mapping of the geomagnetic field has been of intense interest for the past several years. Accurate charts, on a worldwide basis, that describe useful parameters associated with field line geometry could be of extensive use in the study of the inner magnetosphere. Computer models exist today that can trace field lines and can accurately calculate kinematic parameters associated with trapped energetic particles. In many cases, however, a method of quick reference to a complete set of geomagnetic field charts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…From Equations (2) and (3) The coefficients g~" and h m for a given epoch are determined by a least-squares fitting of the model to the databases obtained from the ground, marine, air, and satellite measurements. Including the experimental material for different years makes it possible to evaluate the secular changes of coeff• At present it is assumed (Peddie, 1982;Barraclough, 1987) that the main geomagnetic field for the interval 1945-1985 to be computed from (4) using the appropriate epoch models, with linear interpolation of the coefficients for the intervening dates. The models for the past epochs including 1980.0 constitute the Definitive Models (DGRF), while the 1985.0 coefficients together with a forecast model of the secular variation between 1985.0 and 1990.0 is defined as a Provisional Reference Model (PGRF), so that for the last period g;7(t) = gm (to) + g,m(t --to),…”
Section: The Sources Of the Magnetospheric Magnetic Field And Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Equations (2) and (3) The coefficients g~" and h m for a given epoch are determined by a least-squares fitting of the model to the databases obtained from the ground, marine, air, and satellite measurements. Including the experimental material for different years makes it possible to evaluate the secular changes of coeff• At present it is assumed (Peddie, 1982;Barraclough, 1987) that the main geomagnetic field for the interval 1945-1985 to be computed from (4) using the appropriate epoch models, with linear interpolation of the coefficients for the intervening dates. The models for the past epochs including 1980.0 constitute the Definitive Models (DGRF), while the 1985.0 coefficients together with a forecast model of the secular variation between 1985.0 and 1990.0 is defined as a Provisional Reference Model (PGRF), so that for the last period g;7(t) = gm (to) + g,m(t --to),…”
Section: The Sources Of the Magnetospheric Magnetic Field And Methodsmentioning
confidence: 99%
“…The tables of DGRF and PGRF coefficients are given by Barraclough (1987) (see also IAGA News No. The tables of DGRF and PGRF coefficients are given by Barraclough (1987) (see also IAGA News No.…”
Section: The Sources Of the Magnetospheric Magnetic Field And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modest extrapolations of their results beyond e-folding energies of 40 keV were necessary. We further assumed pitch angle isotropy and incorporated an additional factor of 1.1 into the normalization to compensate for the larger loss cone for southward traveling electrons than for northward traveling electrons on this meridian [Barish and Wiley, 1970]. Table 1 gives the results of these calculations for selected times during 1014-1019 UT.…”
Section: Rapid Temporal Variations the Time Segment 1014-1019mentioning
confidence: 99%
“…Tl;•se electrons then either precipitate or mirror above the northern ionosphere (4). Those that mirror can, in turn, precipitate in the southern ionosphere producing optical auroral emissions (5) stone time AT before or after the scattering VLF waves arrive at the southcrn ionosphere.It should be pointed out thatBarish and Wiley [1970] ha.ve shown that there exists an asymmetry in tl•e mirror poi,t,s at northern and southern ionospheres for charged pa, rticles, a result that follows directly kom considering a. real n•agnetic field model. On the L=4 field line, electrons ,•irror in the north at an altitude 120 km higher th.a.n the mirroring altitude in the south.…”
mentioning
confidence: 96%